Colorectal duplication in adults: report of seven cases and review of the literature. Issue 12 (5th October 2010) - Mourra, Najat; Chafai, Najim; Bessoud, Bertrand; Reveri, Valeria; Werbrouck, Anabelle; Tiret, Emmanuel
Abstract : Background: Gastrointestinal duplications are uncommon congenital abnormalities, usually recognised before the age of 2 (80%). Colorectal duplications (CDDs) occur in only 6.8% of cases, rarely in adults, and are revealed by abdominal pain and intestinal obstruction. Malignant changes are uncommon, but are most often found in the colon. Methods and results: During the last 7 years, the authors have observed seven cases of CDD (three men) with mean age 50.7 years (range 32–73). Four cases were revealed by abdominal pain, and three by intestinal obstruction. Five duplications were located in the caecum, one in the transverse colon, and one in the sigmoid colon. All CDDs were of the cystic type (4.42 cm, range 2–7.5), and three had a communication with the intestinal lumen. All patients except one underwent 'en bloc' resection of the cyst with the adjacent colon. On microscopic examination, CDDs contained multiple layers of the bowel wall, including colonic or small intestinal mucosa. Heterotopic gastric mucosa was observed in only one case, high-grade dysplasia in one case, and low-grade dysplasia in another. No invasive carcinoma was found. Conclusion: Although uncommon, CDDs should be included in the differential diagnosis of all abdominal masses. The treatment approach is excision, in order to avoid any complication. En bloc resection of the colon with CDD may be necessary, because of the intimate attachments of the common wall. Thorough sampling of the specimen is mandatory in order to detect any malignant changes.